The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/odi.12909
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal therapy and endothelial function in coronary artery disease: A randomized controlled trial

Abstract: Periodontal treatment did not provide better vasodilation in patients with coronary disease in a short-term follow-up period, although it maintained blood concentrations of markers of vascular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 34 publications
3
27
0
3
Order By: Relevance
“…In addition, leukocyte-endothelial cell adhesion induced by TNFα leads to an increased production of ROS by said cells [42,43], which promotes leukocyte transmigration to the subendothelial space. Although there is increasing evidence that periodontal treatment can improve endothelial function [44][45][46][47], as far as we know, there are no reports to date about its effect in an obese population. Previous randomized clinical trials have evaluated the effect of periodontal treatment on vasodilation and subclinical arterial thickness in patients with periodontitis in the presence or absence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, leukocyte-endothelial cell adhesion induced by TNFα leads to an increased production of ROS by said cells [42,43], which promotes leukocyte transmigration to the subendothelial space. Although there is increasing evidence that periodontal treatment can improve endothelial function [44][45][46][47], as far as we know, there are no reports to date about its effect in an obese population. Previous randomized clinical trials have evaluated the effect of periodontal treatment on vasodilation and subclinical arterial thickness in patients with periodontitis in the presence or absence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has reported high levels of sICAM -1 in the saliva of individuals diagnosed with periodontal disease. 19 In our study, a significant difference was detected in median salivary TNF -α-R1 concentrations in individuals with obesity (237.38 pg/ml) when compared with healthy individuals (113.11 pg/ml). This may indicate an increase in TNF -α concentrations and could explain the persistent moderate inflammation and a tendency for cell apoptosis in obese patients.…”
Section: What's New?mentioning
confidence: 44%
“…The oxidative stress levels in these patients exhibited a downtrend, returning to normal in 90 days post treatment [142] . Periodontal treatment however did not improve vasodilation in coronary disease patients in a brief follow-up period, even though it maintained the titers of vascular inflammation markers [143] . An in-depth review on oxidative stress in periodontal disease, focusing on the relationship between the local and systemic markers of oxidative stress and periodontal disease is in [144] .…”
Section: Effect Of Periodontal Treatment On Atherosclerotic Inflammationmentioning
confidence: 80%